(Measuring students' awareness of the role of Saudi media in developing awareness of local cultural heritage (Case Study of Hail University Students in Saudi Arabia - Ahmed, Tarek Sayed Abdel Azim; Alhawamdeh, Nabil Zaal Abdelrahman (Journal of Humanities & Social Sciences, 2019)
This study aims to identify the role of mass media in developing the interest of students of the local cultural inheritance. The researchers used the descriptive and analytical approach. To achieve the objectives of the study، (160) questionnaires were distributed to a random sample of students from the University of Ha`il. (SPSS) the Statistical Package for Social Sciences program was used to test the hypotheses of the study. Results of the study showed that the vast majority of respondents agrees to some extent on the role of the media in developing the interest of students of the local cultural inheritance in general. There are no differences between males and females with regard to the role of the media. There is no relationship between the degree of consciousness among the local community in Ha`il of the importance of national heritage and the role of the media in that matter.
Keywords: media; heritage; tourism; awareness